Use of methanol as a potential alternative fuel in a power generation gas turbine - Danielak, Krzysztof; Abbott, David; Sun, Xiaoxiao; Harman-Thomas, James (EDP Sciences, 2025)
Decarbonisation and emissions reduction have become major priorities in industrial power generation. Achieving net-zero greenhouse gas emissions requires adopting alternative fuels such as ammonia, hydrogen, and alcohols, with methanol emerging as a promising candidate. This study investigates the feasibility of using methanol in the SGT5-2000E gas turbine at Killingholme Power Station by modelling the combustion performance of a Siemens Energy Dry Low NOX (DLN) Hybrid Burner, capable of liquid and gaseous fuel operation. A dual-phase strategy is proposed: initial liquid methanol firing to generate sufficient heat for a Waste Heat Recovery (WHR) system, followed by a transition to evaporated methanol. This approach could reduce fuel consumption by 5–6% and reduce NOX emissions. Chemical kinetics modelling of evaporated methanol combustion showed a potential 10% NOX reduction compared to methane, alongside challenges such as increased flashback risk and higher autoignition potential. A key challenge was the increased fuel injection pressure drop due to methanol’s higher mass flow. A RANS (Reynolds-Average Navier-Stokes) CFD (Computational Fluid Dynamics) model was developed, showing that non-uniform nozzle modifications most effectively improved mixing, lowered peak flame temperatures, reduced flashback risk, and significantly decreased NOX emissions. The results highlight the potential for retrofitting turbines for low-carbon bio- and e-methanol combustion, supporting greener energy solutions and longer turbine life. The methanol dual-phase concept shows strong promise for further development.
Keywords: 4004 Chemical Engineering; 40 Engineering; 4017 Mechanical Engineering; 4002 Automotive Engineering; 13 Climate Action; 7 Affordable and Clean Energy